On Lithuanian mathematical olympiads - Mačys, Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2018)
Some problems of Lithuanian school mathematical olympiad 2018 and Vilnius University mathematicalolympiad 2018 are considered. Different methods of solution are compared. Some usefulcommon advices for solving mathematical problems are given.
Keywords: olympiads; solving problems; systems of equations; prime numbers; sequencies